A STUDY ON THE DEMOGRAPHICAL STRUCTURE OF PRE-MODERN TIMES IN SRI LANKA - A.K.C Sewwandi (Paramita: Historical Studies Journal)
The core of this study is to examine the scientific community structure of the pre-modern era of the Sri Lankan society. While this study will be focused only on the migration of people of the Indian and South–East Asian origins to the Western and South-Western regions of Sri Lanka during the specified time period, how the influence of those migrations was reflected on the Sri Lankan architecture of the same period will also be examined. The simultaneous decline of the Rajarata Civilization that lasted for thousands of years uninterrupted and the acceleration of settlements in the Western and the South-Western regions of Sri Lanka in  the 13th century was an outcome of the people who left Rajarata fearing the invasion of  the Kalinga Magha, one of the reasons behind the discontinuation of the Rajarate Administrative System, as well as some regional leaders in Maya and Rohana not supporting the Magha and acting as independent leaders.